Protecting a transgender person’s right to gender identity in the peruvian legal system: from a Dialogical perspective between Constitutional Law and International Human Rights Law: advances, setbacks, and challenges (2014-2018): avances, retrocesos y desafíos (2014-2018) - Rodríguez Campos, Rafael (2018)
In 2014, through Ruling No. 00139-2013-PA/TC, the Constitutional Court (hereinafter, Court) established a constitutional precedent whereby gender is animmutable element and, consequently, it is not possible to request any amendment of data in identity documents. In addition, the Court based its reasoning on the idea that any alteration of identity following that criterion should be construed as a “disorder and/or pathology”. In other words, for this Court (Urviola Hani, Vergara Gotelli, Calle Hayen and Alvarez Miranda, judges who voted in the majority), transsexual persons were “disturbed or sick”. However, in a landmark decision for transgender persons in Peru, the current Court  (Miranda Canales, Ledesma Narváez, Ramos Nuñez and Espinosa-Saldaña Barrera,judges who voted in the majority) issued Ruling No. 06040-2015-PA/TC, by which it strayed away from the constitutional precedent it had set in the previous judgment, guaranteeing the right of access to justice to transgender persons who wish to request the their personal data be updated in their identity documents. In other words, with this decision, the Court recognizes the competence of judges to protect the right to identity and legal personality of transgender persons, as it considers that “there is no longer any impediment, whether legal or jurisprudential, to protecting these rights”.